The Strategic Role of Expatriates in International Human Resource Management on Factors Affecting Global Assignment Success and Failure - Rihansyah, Muhammad Rafi; Nofenti, Gadis; Perkasa, Didin Hikmah (CV. Publikasi Indonesia, 2025)
In the era of globalization, the role of expatriates in International Human Resource Management (IHRM) has become increasingly important, especially for multinational companies operating in various countries. Expatriates not only act as liaisons between headquarters and overseas branches, but also act as agents of change, knowledge transfer, and local network development. However, successful expatriate assignments are not always guaranteed. Challenges such as cultural adaptation, family support, expectation management, and lack of support from the company are often the deciding factors between assignment success and failure. The purpose of this study is to analyze the factors that influence expatriates' success and failure in global assignments. The research method used is library research, by reviewing relevant literature related to the role of expatriates, success, and challenges of global assignments. The results show that expatriate success is influenced by cultural adaptation readiness, family support, training provided, and continuous company support. Conversely, failures often occur due to lack of training, adaptation issues, and poor expectation management. In addition, repatriation management also plays an important role in ensuring expatriates continue to contribute after returning home.